Progress of thematic repositories and megajournals: Perspectives in 2017 - López-Borrull, Alexandre (Anuario ThinkEPI, 2017)
A series of events related to thematic repositories took place in 2016. In this article, the new repositories similar to ArXiv are presented, and their relation to Open Science is described. Likewise, future predictions about megajournals are commented upon. Finally, future trends regarding the strategies of the large information and scientific knowledge companies are analyzed.
Keywords: Disciplinary repositories; megajournals; ArXiv; SocArXiv; SSRN; ChemRxiv; Open science framework.